Metal-responsive promoter DNA compaction by the ferric uptake regulator - Davide Roncarati; Simone Pelliciari; Nicola Doniselli; Stefano Maggi; Andrea Vannini; Luca Valzania; Luca Mazzei; Barbara Zambelli; Claudio Rivetti; Alberto Danielli (Nature Communications, 2016)
The Fur protein regulates transcription of bacterial genes in response to metal ions. Here, the authors show that the Fur protein from Helicobacter pylorirepresses transcription by iron-responsive oligomerization and DNA compaction, encasing the transcriptional start site in a macromolecular complex.